Encountering the Mystery: Essays in Honour of Sergii V. Sannikov on his 70th Birthday. Eds. T. Dyatlyk, O. Geychenko, M. Raber, J.T. Searle, R. Soloviy - Oleksandr GEYCHENKO (Богословські роздуми: Східноєвропейський журнал богословʼя)
Encountering the Mystery: Essays in Honour of Sergii V. Sannikov on his 70th Birthday. Eds. T. Dyatlyk, O. Geychenko, M. Raber, J.T. Searle, R. Soloviy. Rivne: PP “Format-A”, 2020, 284 p.; ISBN 9786175153437 (hbk.); 25.00 USD.